2012
DOI: 10.1039/c2dt30707c
|View full text |Cite
|
Sign up to set email alerts
|

A thiol-mediated active membrane transport of selenium by erythroid anion exchanger 1 protein

Abstract: In this paper, we describe a thiol-mediated and energy-dependent membrane transport of selenium by erythroid anion exchanger 1 (AE1, also known as band 3 protein). The AE1 is the most abundant integral protein of red cell membranes and plays a critical role in the carbon dioxide transport system in which carbon dioxide is carried as bicarbonate in the plasma. This protein mediates the membrane transport of selenium, an essential antioxidant micronutrient, from red cells to the plasma in a manner that is distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…PenSSeSPen could possibly react with various biogenic thiols through the thiol exchange (Fig. 1b) [12,[22][23][24]. The elemental analysis results of PenSSeSPen used in this study were in good agreement with the calculated values.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…PenSSeSPen could possibly react with various biogenic thiols through the thiol exchange (Fig. 1b) [12,[22][23][24]. The elemental analysis results of PenSSeSPen used in this study were in good agreement with the calculated values.…”
Section: Resultssupporting
confidence: 90%
“…We have demonstrated that this species allows reactions with certain endogenous protein thiols through thiol-exchange reactions and participating in the selenium transport (Fig. 1b) [12,[22][23][24]. A better understanding about the metabolism of selenium is also important from the viewpoints of both human health and toxicology, because the range of the selenium intake amount required for a trace nutrient is narrow when compared to some other nutrients [25].…”
Section: Introductionmentioning
confidence: 95%
“…It functions in chloride:bicarbonate exchange, selenium metabolism, volume regulation, erythrocyte cytoskeletal cell structure and metabolic coordination 4547 . Its topology has been controversial, varying from 13 to 16 TMSs, depending on the prediction method used.…”
Section: Resultsmentioning
confidence: 99%
“…When the PenSSeSPen sample was subjected to a MALDI TOF-MS analysis, the distinctive selenium isotopic pattern involving one selenium atom in a molecular ion was detected and the 80 Se-containing molecular ion peak was at m/z 376.3 (Calcd for 80 Se 376.2). PenSSeSPen can react with various biogenic thiols through the thiol-exchange reaction 27,33,34) ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%